Comparative Study on CPAP Compliance: PAP-NAP Followed by CPAP Trial vs. CPAP Trial Alone - Goh, Liang Chye; Rajendram, Nesha; Lim, Bryan Way Wern; Kulasegarah, Jeyanthi; Govindaraju, Revadi; Soo, Chun Ian; Wong, Chee Kuan (Sleep Science, 2025)
To assess the effectiveness of allocating positive airway pressure nap (PAP-NAP) prior to continuous positive airway pressure (CPAP) trial compared with CPAP trial alone in improving CPAP therapy adherence among individuals diagnosed with obstructive sleep apnea (OSA) in our Southeast Asian cohort.A total of 133 adults with OSA were divided into 2 groups: 1 received PAP-NAP before a CPAP trial, and the other underwent a CPAP trial alone. The correlation between CPAP adherence and polysomnographic data was investigated.The PAP-NAP group showed better CPAP compliance (above 90%) and adherence (66.64% ± 31.96%) compared with the CPAP-only group (57.90% ± 34.86%). Both groups experienced reductions in apnea hypopnea index (AHI), with the PAP-NAP group having lower residual AHI. Compliance was defined as usage of CPAP > 4H in 14 days.Positive airway pressure naps prior to a CPAP trial increases short-term CPAP adherence and influences mask selection. Personalized CPAP approaches like PAP-NAP can enhance patient acceptance and motivation. Further research is recommended to investigate long-term adherence.
Keywords: obstructive sleep apnea; CPAP; compliance; adherence; southeastern; Asia